Optic Nerve Ultrasound Evaluation in Idiopathic Intracranial Hypertension - De Bernardo, Maddalena; Vitiello, Livio; De Pascale, Ilaria; Capasso, Luigi; Cornetta, Palmiro; Rosa, Nicola (Frontiers in Medicine, 2022)
Idiopathic intracranial hypertension is a disease with a heterogeneity of possible causes, which needs to be quickly diagnosed. Ocular ultrasonography could be considered an useful tool to diagnose this condition in a fast and non-invasive way. In fact, Karl Ossoinig had already proposed this diagnostic tool in the 1970s for the evaluation of intracranial pressure changes in several pathological conditions, also including idiopathic intracranial hypertension. The aim of this review is to analyze scientific papers published in the last 30 years concerning the use of ocular ultrasonography to assess optic nerve indices in patients with idiopathic intracranial hypertension. Specifically, 15 published articles found in PubMed database were included and analyzed in the present review. Our conclusions suggest that ocular ultrasonography is a reliable diagnostic technique to be utilized in all the cases of suspected raised intracranial pressure. To obtain the best possible accuracy and precision in the least invasive way, standardized A scan seems to be the best choice.